Realizing effectiveness across continents with hydroxyurea: enrollment and baseline characteristics of the multicenter REACH study in Sub-Saharan Africa - McGann, PT; Williams, TN; Olupot-Olupot, P; Tomlinson, GA; Lane, A; Luís Reis da Fonseca, J; Kitenge, R; Mochamah, G; Wabwire, H; Stuber, S; Howard, TA; McElhinney, K; et al. (Wiley, 2018)
Despite its well-described safety and efficacy in the treatment of sickle cell anemia (SCA) in high-income settings, hydroxyurea remains largely unavailable in sub-Saharan Africa, where more than 75% of annual SCA births occur and many comorbidities exist. Realizing Effectiveness Across Continents with Hydroxyurea (REACH, ClinicalTrials.gov NCT01966731) is a prospective, Phase I/II open-label trial of hydroxyurea designed to evaluate the feasibility, safety, and benefits of hydroxyurea treatment for children with SCA in four sub-Saharan African countries. Following comprehensive training of local research teams, REACH was approved by local Ethics Committees and achieved full enrollment ahead of projections with 635 participants enrolled over a 30-month period, despite half of families living >12 km from their clinical site. At enrollment, study participants (age 5.4 ± 2.4 years) had substantial morbidity, including a history of vaso-occlusive pain (98%), transfusion (68%), malaria (85%), and stroke (6%). Significant differences in laboratory characteristics were noted across sites, with lower hemoglobin concentrations (P < .01) in Angola (7.2 ± 1.0 g/dL) and the DRC (7.0 ± 0.9 g/dL) compared to Kenya (7.4 ± 1.1 g/dL) and Uganda (7.5 ± 1.1 g/dL). Analysis of known genetic modifiers of SCA demonstrated a high frequency of α-thalassemia (58.4% with at least a single α-globin gene deletion) and G6PD deficiency (19.7% of males and 2.4% of females) across sites. The CAR β-globin haplotype was present in 99% of participants. The full enrollment to REACH confirms the feasibility of conducting high-quality SCA research in Africa; this study will provide vital information to guide safe and effective dosing of hydroxyurea for children with SCA living in Africa.